2005
DOI: 10.1074/jbc.m504015200
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Apoptosis-inducing Factor, Caspase-activated DNase, and Inhibitor of Caspase-activated DNase to the Nuclear Phenotype and DNA Degradation during Apoptosis

Abstract: We have assessed the contribution of apoptosis-inducing factor (AIF) and inhibitor of caspase-activated DNase (ICAD) to the nuclear morphology and DNA degradation pattern in staurosporine-induced apoptosis. Expression of D117E ICAD, a mutant that is resistant to caspase cleavage at residue 117, prevented low molecular weight (LMW) DNA fragmentation, stage II nuclear morphology, and detection of terminal deoxynucleotidyl transferase staining. However, high molecular weight (HMW) DNA fragmentation and stage I nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
61
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 36 publications
10
61
1
Order By: Relevance
“…2C). The cleavage of ICAD at D117 has been shown to be necessary and sufficient for the release of CAD activity during apoptosis (11). We observed that inhibition of caspase 3 activity attenuated the cleavage of ICAD during myoblast differentiation, confirming that the ICAD partial cleavage stemmed from caspase 3 activity ( ISNT labels methanol-fixed C2C12 nuclei at 12 and 24 h after being switched from growth media (GM) to low-serum differentiation media (DM).…”
supporting
confidence: 58%
See 1 more Smart Citation
“…2C). The cleavage of ICAD at D117 has been shown to be necessary and sufficient for the release of CAD activity during apoptosis (11). We observed that inhibition of caspase 3 activity attenuated the cleavage of ICAD during myoblast differentiation, confirming that the ICAD partial cleavage stemmed from caspase 3 activity ( ISNT labels methanol-fixed C2C12 nuclei at 12 and 24 h after being switched from growth media (GM) to low-serum differentiation media (DM).…”
supporting
confidence: 58%
“…A select handful of nucleases have been implicated in apoptotic DNA fragmentation, and caspase-activated DNase (CAD) is the most characterized (10). CAD is held in check through association with its inhibitor, inhibitor of caspase-activated DNase (ICAD), which is cleaved by caspase 3 to release CAD (10,11). After activation, unobstructed CAD configures into a scissor-like dimer, cleaving DNA with minimal sequence specificity (10,12).…”
mentioning
confidence: 99%
“…Indeed, AIF is a flavoprotein that can oxidize NADH and NADPH in vitro (Miramar et al, 2001) and may participate in the detoxification of reactive oxygen species (Klein et al, 2002) and in the maintenance of glutathione levels (Cande et al, 2004b), although the mechanisms of this antioxidant activity remain to be determined. Upon activation of a serine protease that liberates AIF from its membrane attachment (Polster et al, 2005;Yuste et al, 2005), combined with outer mitochondrial membrane permeabilization, for instance through Bax/Bak-mediated pores (Green and Kroemer, 2004), AIF is released from mitochondria and participates in the catastrophic catabolic process that allows the digestion of the cellular content from within.…”
Section: Introductionmentioning
confidence: 99%
“…Large-scale DNA fragmentation assessment was performed as previously described with some modifications. 58 Briefly, extracted DNA fragments were separated in a 1.0% agarose gel by a pulsed-field gel electrophoresis using a CHEF-DRIII system (Bio-Rad) at 6 V/cm for 20 h at an angle of 120°, with switching times ramped from 5 to 50 s at 14°C. The gel was stained with ethidium bromide and visualized under a UV light.…”
Section: Methodsmentioning
confidence: 99%